Patients' attitudes and preferences towards a freeze-all strategy in ART treatment. Issue 4 (28th February 2019) - Stormlund, S; Schmidt, L; Bogstad, J; Løssl, K; Prætorius, L; Zedeler, A; Pinborg, A
Abstract: STUDY QUESTION: What are the attitudes towards different aspects of a freeze-all strategy and elective frozen embryo transfer (eFET) in comparison with fresh embryo transfer in assisted reproductive technology treatment among female and male patients before and after their first ART treatment cycle in a public health care setting? SUMMARY ANSWER: Despite concerns about the delay in embryo transfer associated with eFET, nearly 60% of the participants were in favor of eFET compared with fresh embryo transfer assuming that the clinical pregnancy rate was equivalent. WHAT IS KNOWN ALREADY: Vitrification and blastocyst transfer have considerably improved success rates after FET with ongoing pregnancy rates in frozen cycles approaching those seen in fresh treatment cycles. Furthermore, the risk of ovarian hyperstimulation syndrome (OHSS) is essentially eliminated in FET cycles, and FET may be beneficial to the endometrial and fetal development because a hormonal environment mirroring the natural cycle is enabled. However, the freeze-all strategy is not yet implemented as standard care. One reason is the presumption of negative patient attitudes towards a freeze-all embryo strategy. So far, no data regarding patients' attitudes on a freeze-all strategy have been published. STUDY DESIGN, SIZE, DURATION: This study was designed as a descriptive cross-sectional study including 165 fertility patients referred for their first ART treatment from December 2014 to June 2016. PARTICIPANTS/MATERIALS, SETTING, METHODS: All newly referred patients participating in a mandatory meeting before initiating ART treatment at the Fertility Clinic, Hvidovre Hospital, Copenhagen, Denmark were requested to fill in an online web-based questionnaire separately for men and women covering attitudes towards a freeze-all strategy, socio-demographic data and reproductive history. The patients were informed about both conventional fresh embryo transfer strategy and the freeze-all strategy prior to answering the questionnaire. MAIN RESULTS AND THE ROLE OF CHANCE: The total response rate was 77.1% ( n = 165), and for women and men respectively 85.8 versus 66.0%. The female respondents were significantly more likely to consider the postponement of embryo transfer difficult compared to the male population (78.6 versus 35.5%; P < 0.001) and they were significantly more willing to accept a risk in treatment on own health to achieve a pregnancy than were the male respondents on their partners health (82.5 versus 96.8%; P = 0.025). However, 59.2% of the women and 59.7% of the men agreed that they would choose eFET over fresh embryo transfer if the chance of pregnancy were the same. Most of the patients furthermore agreed that the health of the mother and their baby was of highest importance. In the adjusted analyses we found no significant predictive factors for preferences towards a freeze-all strategy apart from a negative attitude towards delay of transfer in case of previous unsuccessful ART attempts. LIMITATIONS, REASONS FOR CAUTION: Selection bias cannot be excluded, as the total response rate was 77.1%. The hypothetical nature of the items may furthermore limit the validity of the results. In addition, the participants were from a single Fertility Clinic in the Capital Region of Denmark and may therefore not be representative for all fertility patients. WIDER IMPLICATIONS OF THE FINDINGS: In a clinical setting with similar pregnancy rates for eFET and fresh embryo transfer, these results indicate that patients, when given access to information on advantages and disadvantages of both fresh embryo transfer and eFET, are less prone to opt for fresh embryo transfer. This may be ground breaking for a patient-centered paradigm shift in routine ART treatment with a wider implementation of a freeze-all and eFET-strategy eliminating the risk of OHSS. STUDY FUNDING/COMPETING INTEREST(S): The Danish Council for Independent Research and Merck Serono supported the study. The study is part of the Reprounion Collaborative study, co-financed by the European Union, Interreg V ÖKS. No competing interests exist.